Analisis Proses Perencanaan Penyusunan Perda Pendidikan di DPRD Kabupaten Solok Selatan - Savitri Sindi Dwi (CV. ITTC INDONESIA, 2025)
This study aims to analyze the planning process for the preparation of Regional Regulations (Perda) on Education in the DPRD of South Solok Regency. The method used is qualitative with data collection techniques through document studies and observations of the legislative process. The results of the study indicate that the planning for the preparation of Regional Regulations on Education is carried out through the Regional Regulation Formation Program (Propemperda), which involves the DPRD, Regent, regional apparatus, and community participation. The main stages in this process include data collection, preparation of academic papers, and public discussions. Discussion of the Draft Regulation takes place at two levels, namely level I discussions which include the delivery of views from the DPRD and Regent, then continued with level II discussions which culminate in decision making in a plenary meeting. The dissemination of the Regulation is carried out by the DPRD and the Regional Government in order to provide information and accommodate public input. This study confirms that the success of the preparation of the Regional Regulation on Education depends on good coordination between various stakeholders and active community involvement in the legislative process.